Synthesis and Exploring the Structural, Electrical and Optical Characteristics of PVA/TiN/SiO2 Hybrid Nanosystem for Photonics and Electronics Nanodevices - Hussien, Huda Abdul Jalil; Hashim, Ahmed (Journal of inorganic and organometallic polymers and materials, 2023)
This work aims to explore the structural, dielectric and optical properties of titanium nitride (TiN)/silicon dioxide (SiO 2 ) nanostructures doped polyvinyl alcohol(PVA) to utilize in several electronics and photonics nanodevices. The dielectric characteristics were investigated in frequency (f) range from 100 Hz to 5 × 10 6 Hz. The results of dielectric properties displayed that the dielectric constant and conductivity of PVA increased about 17.4% and 58.7% respectively at f = 1 kHz when the content of TiN-SiO 2 NPs reached 6wt.% with low values of dielectric loss which made it can be considered as a key for various nanodielectrics devices and energy storage fields. The dielectric parameters of PVA/TiN-SiO 2 nanocomposites were changed as the frequency increased. The optical properties were studied at wavelength (λ) ranged (200–800) nm. The absorbance of PVA was rise about 97.5% with adding of 6 wt.% of TiN-SiO 2 NPs and the optical conductivity increased about 98.7% at λ = 500 nm, this performance make them as promising materials in various optical and electronics fields like photocatalysis, optoelectronics and solar cells applications. The energy gap was reduced from 4.5 eV for pure polymer to 1.8 eV when the content of TiN-SiO 2 NPs reached 6wt %. The results of other optical parameters enhanced with rise in the concentration of TiN-SiO 2 NPs. Finally, the results demonstrated that the (PVA-TiN-SiO 2 ) nanostructures can be considered as promising materials in the nanodielectrics and photonics applications with individual characteristics included low cost, flexible, lightweight, excellent optical and electronic properties compare with other nanocomposites.